2007
DOI: 10.1083/jcb.200607084
|View full text |Cite
|
Sign up to set email alerts
|

The UNC-45 chaperone mediates sarcomere assembly through myosin degradation inCaenorhabditis elegans

Abstract: Myosin motors are central to diverse cellular processes in eukaryotes. Homologues of the myosin chaperone UNC-45 have been implicated in the assembly and function of myosin-containing structures in organisms from fungi to humans. In muscle, the assembly of sarcomeric myosin is regulated to produce stable, uniform thick filaments. Loss-of-function mutations in Caenorhabditis elegans UNC-45 lead to decreased muscle myosin accumulation and defective thick filament assembly, resulting in paralyzed animals. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
117
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 36 publications
12
117
1
Order By: Relevance
“…Early work performed on this chaperone in the C. elegans model indicates that the ratio of myosin heavy chain protein levels to Unc45 is critical for proper muscle function. Worms either over-or underexpressing Unc45 show accelerated degradation of myosin heavy chains via the ubiquitin-proteasome system, supporting the hypothesis that the correct ratio between myosin heavy chain and its chaperone is important for stable myosin filament formation (8).…”
supporting
confidence: 53%
See 2 more Smart Citations
“…Early work performed on this chaperone in the C. elegans model indicates that the ratio of myosin heavy chain protein levels to Unc45 is critical for proper muscle function. Worms either over-or underexpressing Unc45 show accelerated degradation of myosin heavy chains via the ubiquitin-proteasome system, supporting the hypothesis that the correct ratio between myosin heavy chain and its chaperone is important for stable myosin filament formation (8).…”
supporting
confidence: 53%
“…These data may explain why calponin is turned over along with other thick filament components. Although previous work in C. elegans indicated that any alteration in the ratio of Unc45 to myosin heavy chain expression led to ubiquitination and degradation of myosin heavy chain (8), treatment with a proteasome inhibitor did not induce accumulation of contractile proteins in SM1 cells. Instead, inhibition of autophagy blocked degradation of contractile proteins in the SM1 cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…If this separation between pulses is much shorter than chaperone half-life, the excess of chaperones will be beneficial, because it will reduce the U max during the response to the following pulse (data not shown). Thus, the excess of chaperones can be both protective or toxic, depending on the context of the environment: this observation is indirectly supported by chaperone overexpression studies (14,15,17,18).…”
Section: Resultsmentioning
confidence: 83%
“…Chaperones and proteases maintain the concentration of unfolded proteins at low levels. However, excessive accumulation of chaperones can be toxic when out of proportion to the amount of unfolded proteins (14,15). To capture these 2 physiological aspects in our model we compare the quality of the response in the presence and absence of the TA mechanism by monitoring (i) how well it can minimize the levels of U and (ii) how effective the response is in preventing excessive accumulation of chaperones.…”
Section: Resultsmentioning
confidence: 99%